Glacial δ13C decreases in the western South Atlantic forced by millennial changes in Southern Ocean ventilation - Campos, Marília C.; Chiessi, Cristiano M.; Voigt, Ines; Piola, Alberto R.; Kuhnert, Henning; Mulitza, Stefan (Copernicus GmbH, 2016)
Abrupt millennial–scale climate change events of the last deglaciation (i.e., Heinrich Stadial 1 and the Younger Dryas) were accompanied by marked increases in atmospheric CO2 presumably originated by outgassing from the Southern Ocean. However, information on the preceding Heinrich Stadials during the last glacial period is scarce. Here we present stable carbon isotopic data (delta 13C) from two species of planktonic foraminifera from the western South Atlantic that reveal major decreases (up to 1‰) during Heinrich Stadials 3 and 2. These delta 13 C decreases are most likely related to millennial– scale periods of intensification in Southern Ocean deep water ventilation presumably associated with a weak Atlantic meridional overturning circulation. After reaching the upper water column of the Southern Ocean, the delta 13C depletion would be transferred equatorward via central and thermocline waters. Together with other lines of evidence, our data are consistent with the hypothesis that the CO2 added to the atmosphere during abrupt millennial–scale climate change events during the last glacial period also originated in the ocean and reached the atmosphere by outgassing from the Southern Ocean. The temporal evolution of delta 13C during Heinrich Stadials in our records is characterized by two relative minima separated by a relative maximum. This “w–structure” is also found in North Atlantic and South American records, giving us confidence that such structure is a pervasive feature of Heinrich Stadial 2 and, possibly, also Heinrich Stadial 3.